Emotional intelligence towards work-life balance among working women in federal territory of Kuala Lumpur - Lor, Gia Shin (Universiti Malaysia Sarawak (UNIMAS), 2019)
Emotional intelligence is said to be one of the individual factors that is capabale of affecting a person's degree of work-life balance. In Malaysia, the number of working women leaving their jobs has been rather alarming. Acknowledged with the significant contribution of women to the economy, this issue warrants immediate attention. The aim of this research was to examine the association between emotional intelligence and work-life balance of working women in Federal Territory of Kuala Lumpur, and the result of which is to be generalized to a bigger population - working women im Malaysia. The framework of emotional intelligence in this study is adopted from Goleman's Framework of Emotional Intelligence that comprises four learned competencies - self-awareness, self-management, social awareness and relationship management. The dimensions work-life balance applied on the other hand are work-family conflict, family-work conflict, family satisfaction, and work satisfaction. Questionnaires from past studies on emotional intelligence and work-life balance were adopted and modified. The data collected from 382 respondents were analyzed quantitatively. The relationship between the independent variable - level of emotional intelligence of the working women, and dependent variable - level of work-life balance of the working women is tested using Pearson Correlation Coefficient.